Independent Music Label Business Transformation To Digitalization In Indonesia (Case Study : MDX Records) - Taufik Hidayat (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
MDX Records is one of Indie Label which has published music albums both physically dan digitally located in Cimahi, West Java, Indonesia as the subject raised in this study. Comparing the effectiveness and efficiency of the Indie label business which is carried out in conventional and digital ways is aim of this study. Data collection stage by reviewing literature data on indie music, technological developments, and business digitalization which are considered related to the research topic, The author met face to face and conducted a direct interview the Owner and Producer of MDX Records to obtain valid and actual information from business people who were the object of research, and Documentation by using media such as cellphones for photos, videos, and sound recorders to record interviews to get information about the indie music industry and the development of digital technology. With the development of technology, especially in the music business, it has a very positive impact on the progress of the Indie Label business in Indonesia. With the advancement of technology, Talent Search, Music Production and Album Distribution which was previously very limited in scope, time, energy, and cost, can now be done at a much lower cost.